Introduction of an Electronic Forum for Annual Development Planning (A Case Study in Banyuasin Regency, South Sumatra, Indonesia) - Irwanto Irwanto (Indonesian Journal of Environment and Sustainable Development, 2013)
Indonesian constitution was amended in 1999 and requested for local government to establish bottom up planning process that has been set as a standard approach to accommodate local aspiration in the making of annual development plan. The Musrenbang (Musyawarah Perencanaan Pembangunan/The Deliberation of development Plan) was amended by Law No. 25/2004 as the stages of planning formulation process in which stakeholders and Public Administrator sit down for forum to communicate each other to find best means for local problem solution. Musrenbang need to modify since it tend to not work as become effective mechanism to accommodate aspirations of stakeholders (bottom level) and hand them over to local government (upper level) due to several barriers, such as; geographical distance, limited transportation system, irregular political intervention and bureaucratic red tape. Using Information Communication Technology (ICT) that able to simplify the planning process by utilizing the people’s interactions expectedly can make simpler and faster procedure, including maximizing the role of Musrenbang. An Electronic forum for annual development planning will set to improve validity, effectiveness and efficiency. Banyuasin Regency, South Sumatera, Indonesia is now making preparation to introduce this system. PCM method was applied to analyze the problems for its introduction. Keywords: development plan, information communication technology, local government, musrenbang.